Multiwall carbon nanotube sensor for monitoring engine oil degradation - Moon, Seung-Il; Paek, Kyeong-Kap; Lee, Yun-Hi; Kim, Jai-Kyeong; Kim, Soo-Won; Ju, Byeong-Kwon (ELECTROCHEMICAL SOC INC, 2006)
An engine oil condition sensor based on multiwall carbon nanotubes was fabricated with the screen printing method. Carbon nanotube (CNT) paste was printed between two parallel-aligned electrodes. The conductivity change in the engine oil according to mileage was measured by using CNT oil sensor. The sensor output was compared with total acid number (TAN) to determine the remaining useful life of the engine oil. It was found that the sensor output was closely similar to TAN of the engine oil. As a result, a real-time engine oil condition monitoring sensor can be realized using CNTs as sensitive materials. (c) 2006 The Electrochemical Society.
Keywords: ELECTRONIC-PROPERTIES; ROOM-TEMPERATURE